2015
DOI: 10.1002/elsc.201500019
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of lignocellulosic biomass from animal manure as a means of enhancing biogas production

Abstract: Biogas produced from lignocellulosic biomass, e.g. animal manure, has the potential to be a promising renewable energy source. Special emphasis has been placed on animal manure pretreatment in an anaerobic digestion as a means of enhancing biogas yield. Here, we review the existing pretreatment methods of anaerobic digestion with regard to their effects on the conversion of animal manure to biogas. Various methods and their challenges are highlighted. The effects of pretreatment are complex and usually depend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Previously, several studies have shown that NaOH pretreatment was effective and improved the methane yields of lignocellulosic biomass and livestock manures. For instance, NaOH pretreatment improved the methane yields of wheat straw from 39 to 112% 48 and by 46 and 26% for poultry and cattle manure, respectively 24 . Similarly, Liu et al 45 .…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Previously, several studies have shown that NaOH pretreatment was effective and improved the methane yields of lignocellulosic biomass and livestock manures. For instance, NaOH pretreatment improved the methane yields of wheat straw from 39 to 112% 48 and by 46 and 26% for poultry and cattle manure, respectively 24 . Similarly, Liu et al 45 .…”
Section: Resultsmentioning
confidence: 90%
“…The improved methane yields after an alkaline pretreatment is due to the delignification of the lignocellulosic biomass and solubilization of organic matter. Previous studies have shown that during NaOH pretreatment the accessibility of holocellulose is increased and is closely related to delignification 24 . The removal of lignin will lead to considerable change in the microstructure of the cell wall and thereby increase the accessibility of cellulose and hemicelluloses to anaerobic microorganisms and so their biodegradability 23,49 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), and c surface area of each char. The yield and surface area are based on a single measurement, whereas the pH was obtained from triplicate measurements while manures consist of partially digested lignocellulose, nitrogen, phosphorus, and alkali metals (Muhammad Nasir and Mohd Ghazi 2015;Shen et al 2015). Thus, the chemical composition of the precursors is likely to contain a mixture of organic, inorganic, and lignocellulosic components.…”
Section: Characterization Of the Surface Functionalitiesmentioning
confidence: 99%
“…Typically, only 60% of the cellulose content of manure is converted to methane, while the rest leaves the digester because it is inaccessible to the microorganisms since it is protected by lignin. Therefore, the methane yield is also low compared to other feedstocks [19].…”
Section: Introductionmentioning
confidence: 98%